Mindsets and EFL Learner Autonomy in the Digital Era : Secondary School Learners as a Case Study - khoudri, insaf (International Journal of Language and Literary Studies, 2024)
EFL learners in Morocco have numerous online resources and tools at their disposal to aid in language learning. Despite this abundance, many learners face challenges in developing learner autonomy and effectively utilizing these digital tools. Mindsets are often attributed to these difficulties and can have a significant impact on success or failure in language learning. The mode of learning to which students are exposed also plays a role. This paper aims to enhance understanding of the relationship between mindset, mode of learning, and learner autonomy in Moroccan EFL education. A self-administered questionnaire was given to two groups of 88 Moroccan Second-year baccalaureate students to investigate whether mindsets or mode of learning affects autonomy in the technological era. The findings demonstrated that the majority of students had mobile phones, but their usage varies. Project-based learners demonstrated a high level of autonomy, with 93% using mobile phones for research and learning instead of social media. Conversely, 20% of teacher-centered learners believed a teacher’s presence is necessary, while all project-based learners considered the teacher’s role important but not always required. The study highlighted the importance of mindset and mode of learning in developing learner autonomy and the potential benefits of project-based learning for language learners.